Analisis Sensitivitas dalam Optimasi Keuntungan Produksi Kue Ulang Tahun dengan Metode Branch and Bound - Monalisa Ismail; Novianita Achmad; Sri Lestari Mahmud (Euler : Jurnal Ilmiah Matematika, Sains dan Teknologi, 2022)
The increasingly rapid development of the business world requires companies engaged in industry, trade, and services to continue to optimize their business activities to win the market competition. Mikaila Bakery is one of the businesses producing birthday cakes in Gorontalo Province. In the birthday cake business at Mikaila Bakery, so far, the amount of production is only determined by estimates, so profits do not reach optimal profits. This study aimed to determine the optimal profit obtained in the production of birthday cakes at Mikaila bakery using the branch and bound method and to determine the results of sensitivity analysis to changes in the objective function coefficients and constraint functions in the branch and bound method. The analysis results show that using the branch and bound method, Mikaila Bakery's cake shop gets an optimal profit of Rp. 38,433,000 per month or an increase of Rp. 3.4% of the previous profit. The results of the sensitivity analysis show that profits will remain in optimal conditions if the birthday cake business at Mikaila Bakery follows the changes that occur in the coefficient of the objective function and the constraint function based on the upper bound and lower bound according to the output. Which has been generated using POM-QM software.